NDG Community Action Plan 2014 - NDG Community Council (NDGCC) (2014)

Annual Report : 2013–2014 - NDG Community Council (NDGCC) (2014)

Housing Resources - NDG Community Council (NDGCC) (2014)

Housing Resources - NDG Community Council (NDGCC) (2014)

NDG Community Strategic Plan 2013-2016 - NDG Community Council (NDGCC) (2014)

Newly Arrived in NDG : Resource Guide - NDG Community Council (NDGCC) (2014)

Nouvellement arrivé à NDG : Guide des ressources - NDG Community Council (NDGCC) (2014)

Rapport annuel : 2013–2014 - NDG Community Council (NDGCC) (2014)

Westhaven Sector NDG Montreal - NDG Community Council (NDGCC) (2014)
The Westhaven sector is one of the four identified vulnerable sectors in Notre-Dame de Grace. Saint- Jacques and Sherbrooke Street on the East and West and West Broadway and Connaught on the North and South side bind this neighbourhood. The NDG Community Council approached various stakeholders and key actors within the community including residents, volunteers, employees and private storeowners in order to voice their concerns and visions for Westhaven.